On the clinical relevance of using complete high-resolution HLA typing for an accurate interpretation of posttransplant immune-mediated graft outcomes - Meneghini, Maria; Perona, Anna; Crespo, Elena; Bemelman, Frederike; Reinke, Petra; Viklicky, Ondrej; Giral, Magali; Palou, Eduard; Torija, Alba; Donadeu, Laura; Melilli, Edoardo; Zuñiga, Jose; et al. (Frontiers in Immunology, 2022)
Complete and high-resolution (HR) HLA typing improves the accurate assessment of donor–recipient compatibility and pre-transplant donor-specific antibodies (DSA). However, the value of this information to identify de novo immune-mediated graft events and its impact on outcomes has not been assessed. In 241 donor/recipient kidney transplant pairs, DNA samples were re-evaluated for six-locus (A/B/C/DRB1/DQB1+A1/DPB1) HR HLA typing. De novo anti-HLA antibodies were assessed using solid-phase assays, and dnDSA were classified either (1) as per current clinical practice according to three-locus (A/B/DRB1) low-resolution (LR) typing, estimating donor HLA-C/DQ typing with frequency tables, or (2) according to complete six-locus HR typing. The impact on graft outcomes was compared between groups. According to LR HLA typing, 36 (15%) patients developed dnDSA (LR_dnDSA+). Twenty-nine out of 36 (80%) were confirmed to have dnDSA by HR typing (LR_dnDSA+/HR_dnDSA+), whereas 7 (20%) did not (LR_dnDSA+/HR_dnDSA−). Out of 49 LR_dnDSA specificities, 34 (69%) were confirmed by HR typing whereas 15 (31%) LR specificities were not confirmed. LR_dnDSA+/HR_dnDSA+ patients were at higher risk of ABMR as compared to dnDSA− and LR_dnDSA+/HR_dnDSA− (logRank < 0.001), and higher risk of death-censored graft loss (logRank = 0.001). Both LR_dnDSA+ (HR: 3.51, 95% CI = 1.25–9.85) and LR_dnDSA+/HR_dnDSA+ (HR: 4.09, 95% CI = 1.45–11.54), but not LR_dnDSA+/HR_dnDSA− independently predicted graft loss. The implementation of HR HLA typing improves the characterization of biologically relevant de novo anti-HLA DSA and discriminates patients with poorer graft outcomes.